Site-specifically modified ribosomal RNAs - Chow, Christine (Henry Stewart Talks, 2008)
Background on modified RNAs, Approaches for generating site-specifically modified RNAs, Examples of modifications (pseudouridine) in the ribosome, Biophysical studies on site-specifically modified RNAs representing helix 69 of the ribosome
Reviewed at 2021/06/30